UV-C light: A powerful technique for inactivating microorganisms and the related side effects to the skin - Monthanat Ploydaeng (2020)
© 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Hospital-associated infections have led to a significant increment of morbidity and mortality among patients. As a result, the public health had concentrated on preventing the transmission of infection using environmental controls. UV-C radiation or ultraviolet germicidal irradiation (UVGI) had caught interest for decades as it can potentially degrade many kinds of microorganisms. This review aims to highlight the current information regarding the ability of UV-C radiation in terms of disinfection and focuses on its application and safety in the medical field.